Accounting for Sustainability: Building Awareness among Elementary School Student through International Community Service - Maharani, Astrid; Soraya, Zalkha; Nursaid; Haryani, Sri; Nooh, Samuel Andri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Building Awareness among Elementary School student through International Community Service", was implemented at Permai Pulai Pinang, Malaysia, with elementary school students as the main partners. The program was designed to enhance student’ knowledge, awareness, and skills in understanding the role of accounting as a tool for promoting sustainability. In an era where environmental, social, and economic challenges are increasingly complex, the younger generation must be equipped with literacy in sustainability-oriented financial accountability.The activities were carried out through interactive workshops, group discussions, and practical exercises that introduced concepts of sustainable development, green accounting, and responsible financial practices. Student were actively engaged in problem-solving sessions and case studies relevant to their daily lives, thereby linking abstract accounting concepts to real-world sustainability issues. The international setting of this program also provided cross-cultural learning opportunities, encouraging participants to exchange perspectives and develop a global mindset toward sustainability challenges.The outcomes of the program showed increased awareness and understanding among participants about the importance of integrating sustainability principles into decision-making processes. Furthermore, the program fostered critical thinking, collaboration, and social responsibility among the student. This initiative demonstrates that accounting education, when integrated with sustainability values, can serve as a powerful medium to inspire the younger generation to become agents of change for a sustainable future. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 17: Partnerships for the Goals